Enforcement of Government Regulation in Lieu of Law No. 51 of 1960 concerning the Prohibition of Unauthorized Use of Land (Case Study: The Banks of the Sepak Gabus River): Penegakan UU 51 Prp 1960 Atas Penguasaan Tanah Tanpa Hak (Studi Kasus: Bantaran Sungai Sepak Gabus) - Nadya Faradiba; Yuwono Prianto (Universitas Muhammadiyah Sidoarjo, 2025)
General background: Illegal land occupation along riverbanks remains a persistent challenge in urban areas, threatening ecological functions and legal order. Specific background: In the Sepak Gabus River, Bekasi Regency, hundreds of buildings have been constructed without legal rights, violating Government Regulation in Lieu of Law No. 51 of 1960 and disrupting the river’s environmental capacity. Knowledge gap: Existing studies mainly adopt normative approaches, leaving limited empirical analysis on how legal enforcement, institutional capacity, and community dynamics interact in real implementation. Aims: This study examines the legal basis, enforcement mechanisms, and barriers faced by local government in addressing unlawful land occupation in riverbank areas. Results: Findings show that all structures lack valid land rights, while enforcement remains ineffective due to inconsistent implementation, limited relocation facilities, social resistance, weak coordination, and a permissive legal culture shaped by long-term state neglect. Novelty: This research integrates empirical field data with Roscoe Pound’s social engineering theory and Soekanto’s law-effectiveness framework to explain why regulatory enforcement fails in environmentally critical zones. Implications: Strengthening inter-agency coordination, ensuring adequate relocation support, and fostering legal awareness are essential to restore riverbank ecological functions and enhance sustainable land governance. Highlights: The study reveals that all riverbank structures lack legal land rights and constitute illegal occupation. Law enforcement remains weak due to limited facilities, inconsistent action, and community resistance. An integrated strategy is required to restore ecological functions and improve legal compliance. Keywords: Land Occupation, Riverbanks, Law Enforcement, UU 51 Prp 1960